Knowledge, attitudes, practices and fear of COVID‐19 among Iranians: A quick online survey. (23rd April 2021) - Ghaderi, Ebrahim; Mahmoodi, Hassan; Sharifi saqqezi, Pershang; Ghanei Gheshlagh, Reza; Moradi, Ghobad; Shokri, Azad; Piroozi, Bakhtiar; Mohamadi Bolbanabad, Amjad; Ahmadi, Asad
Abstract: To control COVID‐19, several strategies were proposed in Iran since the start of the outbreak. The number of reported infected people and its consequent death toll herald relative inadequacies in the quality and extent of the measures in curbing the COVID‐19 transmission cycle. This study was conducted to investigate knowledge, attitude, precautionary practices and degree of fear related to COVID‐19 in a sample of Iranian population. This study was conducted among 457 residents of Kurdistan Province, Iran, through social networks and social media (WhatsApp and Telegram). Knowledge, attitude and practice and fear of COVID‐19 were collected using valid tools. Multiple logistic regression and multivariate linear regression analyses were used to identify factors associated with binary outcome attitudes, practices and continuous variables knowledge and fear of COVID‐19, respectively. The mean ( SD ) age of participants was 37.86 (10.42); of them, 252 (55.1%) were men, and more than two‐thirds were married (74.8%). About 10% of the respondents were in believed that COVID‐19 could create a type of social stigma. Level of knowledge about COVID‐19 in 77.8% of the study attendees was acceptable, and 352 of them (70%) were confident that the virus would eventually be successfully controlled in the world, but only 252 of the attendants (50%) had confidence about successful control of COVID‐19 in Iran. Applying multiple logistic regression, knowledge (OR: 1.18, p  = 0.028) and fear (OR: 1.04, p  = 0.028) of COVID‐19 were associated with positive attitude towards controllability of COVID‐19. Gender (OR: 1.96, p  = 0.012), sources of information (OR: 5.00, p  = 0.005) and knowledge (OR: 1.27, p  = 0.006) were also indicated association with taking precautionary practices to control COVID‐19. Further studies are recommended to boost level of knowledge, strengthen positive attitude and ameliorate behavioural pattern for successful control of COVID‐19 in Iran.